Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Produktivitas Karyawan: Studi Kasus Pada Karyawan Bagian Produksi CV Putra AR Ciamis - Nur Muhammad Ali Wildani; Ari Arisman; Nita Fauziah Oktaviani (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the simultaneous and partial influence of work discipline and work environment on the work productivity of employees in the production department of the company CV Putra AR Ciamis. The research method used is a quantitative research method with a survey approach. The sampling technique used saturated samples with a sample size of 70 people. The data collection technique uses an offline questionnaire. The data used is primary data. The analytical tool used in this research is multiple regression using SPSS 25. The research results show that simultaneously work discipline and the work environment have a significant effect on productivity. Partially, work discipline has a significant effect on work productivity. Partially, the work environment has a significant effect on work productivity.